Regulation of Ion Channel Function in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes by Cancer Cell Secretion Through DNA Methylation - Zhong, Rujia; Zhang, Feng; Yang, Zhen; Li, Yingrui; Xu, Qiang; Lan, Huan; Lang, Siegfried; Cyganek, Lukas; Burgermeister, Elke; El-Battrawy, Ibrahim; Zhou, Xiaobo; Akin, Ibrahim; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac dysfunction including arrhythmias appear frequently in patients with cancers, which are expected to be caused mainly by cardiotoxic effects of chemotherapy. Experimental studies investigating the effects of cancer cell secretion without chemotherapy on ion channel function in human cardiomyocytes are still lacking. Methods The human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) generated from three healthy donors were treated with gastrointestinal (GI) cancer (AGS and SW480 cells) medium for 48 h. The qPCR, patch-clamp, western blotting, immunostaining, dot blotting, bisulfite sequence, and overexpression of the ten-eleven translocation (TET) enzyme were performed for the study. Results After treated with cancer cell secretion, the maximum depolarization velocity and the action potential amplitude were reduced, the action potential duration prolonged, peak Na+ current, and the transient outward current were decreased, late Na+ and the slowly activating delayed rectifier K+ current were increased. Changes of mRNA and protein level of respective channels were detected along with altered DNA methylation level in CpG island in the promoter regions of ion channel genes and increased protein levels of DNA methyltransferases. Phosphoinositide 3-kinase (PI3K) inhibitor attenuated and transforming growth factor-β (TGF-β) mimicked the effects of cancer cell secretion. Conclusions GI cancer cell secretion could induce ion channel dysfunction, which may contribute to occurrence of arrhythmias in cancer patients. The ion channel dysfunction could result from DNA methylation of ion channel genes via activation of TGF-β/PI3K signaling. This study may provide new insights into pathogenesis of arrhythmia in cancer patients.